The use of online annotations in reading instruction and its impact on students' reading progress and processes. Issue 1 (8th April 2016) - Yeh, Hui-Chin; Hung, Hsiu-Ting; Chiang, Yu-Hsin
Abstract: Studies suggest that the incorporation of online annotations in reading instruction can improve students' reading comprehension. However, little research has addressed how students use online annotations in their reading processes and how such use may lead to their improvement. This study thus adopted Reciprocal Teaching (RT) as an instructional framework to support students' reading comprehension progress and processes, facilitated by the use of online annotations. A total of 54 English language learners at a university were recruited to read with online annotations based on the RT procedure, namely predicting, clarifying, questioning, and summarizing. The data collected included the students' scores on pre- and post-tests and their participation records in a collaborative learning environment. The results reveal that the students enhanced their reading comprehension after the intervention. Their reading processes were also analyzed, and the major differences between the groups making more and less progress were identified. Those who made more progress not only frequently reviewed their previously generated predictions, clarifications, questions, and summaries but also actively provided feedback to their peers in a reciprocal manner. Pedagogical implications and recommendations are discussed.